SNAILS AND SLUGS - JIE YING, LEE; Mohd Effendi, Marzuki; Camilia Yen, Richard; Mohd Zacaery, Khalik (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
The phylum Mollusca is the second most diverse animal phylum in the world, after the Arthropoda. Within the former, the order Gastropoda, comprising singleshelled organisms (conspicuous to reduced shells), is represented by an estimated 500 species in Sarawak.